2019
DOI: 10.1371/journal.pone.0217822
|View full text |Cite
|
Sign up to set email alerts
|

RNA virus spillover from managed honeybees (Apis mellifera) to wild bumblebees (Bombus spp.)

Abstract: The decline of many bumblebee species ( Bombus spp.) has been linked to an increased prevalence of pathogens caused by spillover from managed bees. Although poorly understood, RNA viruses are suspected of moving from managed honeybees ( Apis mellifera ) into wild bumblebees through shared floral resources. We examined if RNA viruses spillover from managed honeybees, the extent to which viruses are replicating within bumblebees, and the role of flowers in transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
130
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(149 citation statements)
references
References 43 publications
4
130
3
Order By: Relevance
“…In case of the European honey bee, Varroa-mediated high DWV titres in bees may cause spill overs and promote virus spread to associates and other pollinators [63]. The presence of apiaries has shown to cause a high prevalence of DWV and BQCV in wild pollinators [19] and species associated with beehives [10,13,64]. We found BQCV in honey bees but no other pollinator, which may be due to the higher BQCV prevalence in honey bees compared to other bees [65], and the low number of wild bee pollinators in our sample set.…”
Section: Pathogen Reservoir and Viral Spill Over Into Wild Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In case of the European honey bee, Varroa-mediated high DWV titres in bees may cause spill overs and promote virus spread to associates and other pollinators [63]. The presence of apiaries has shown to cause a high prevalence of DWV and BQCV in wild pollinators [19] and species associated with beehives [10,13,64]. We found BQCV in honey bees but no other pollinator, which may be due to the higher BQCV prevalence in honey bees compared to other bees [65], and the low number of wild bee pollinators in our sample set.…”
Section: Pathogen Reservoir and Viral Spill Over Into Wild Populationsmentioning
confidence: 99%
“…Increasing evidence suggests that many of these pathogens are not specific to honey bees and instead are shared between many pollinator species and associated arthropods, including bumble bees and other wild bees [10][11][12]; bee predators, such as wasps [10,11]; and scavenging insects, such as ants, cockroaches, and beetles [10,[13][14][15]. Many of these host species have been found cohabiting in bee hives [13,15,16] or share floral resources with honey bees [17][18][19][20]. Although arthropods harbour an enormous diversity of viruses [21,22], little is known about the host range and dynamics of viruses within pollinator communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scattered information suggests that some of these viruses are not to be restricted to honey bees, but also infect and replicate in other members of the Apidae family. Spill-over events from managed honey bees into bumblebee species have been described for DWV, BQCV, ABPV, SBV and Lake Sinai viruses (LSV) (27)(28)(29)(30), whereas honey bee viruses have also been described in ants (Formicidae) (31) and wasps (Vespidae) (32). Recent advancements in sequencing technologies and metagenomics have accelerated virus discovery in bees and a number of studies have attempted to describe the viral diversity associated with bees.…”
Section: Introductionmentioning
confidence: 99%
“…Deformed wing virus (DWV) is undergoing a global epidemic in honeybees and is an emerging disease in bumblebees (Fürst et al, 2014;Manley et al, 2019;Wilfert et al, 2016); its prevalence and viral load is highest in honeybees (Apis mellifera). Black queen cell virus (BQCV) is also closely linked with honeybees (McMahon et al, 2015) but with high prevalence and viral load found across bumblebee species, particularly when apiaries are present in the area (Alger, Burnham, Boncristiani, & Brody, 2019). Slow bee paralysis virus (SBPV) on the other hand shows higher prevalence and viral load in bumblebee species than in honeybees (McMahon et al, 2015).…”
mentioning
confidence: 99%